Prenatal Depression and Its Associated Risk Factors Among Pregnant Women in Bangalore: A Hospital Based Prevalence Study - Sheeba, B.; Nath, Anita; Metgud, Chandra S.; Krishna, Murali; Venkatesh, Shubhashree; Vindhya, J.; Murthy, Gudlavalleti Venkata Satyanarayana (Frontiers in Public Health, 2019)
BACKGROUND The most common psychological problem that affects a woman during her perinatal period worldwide is depression. The risk of prenatal depression increases significantly as pregnancy progresses and clinically significant depressive symptoms are common in mid and late trimesters. Studies from various countries around the world have shown a prevalence rate ranging from as low as 4% to as high as 81%. The prevalence of depression in India is shown to vary from 9.18% in one study to 36.75 % reported in another. There is paucity of research on depression during the prenatal period, especially in India. Given this background, the present study aimed to assess the prevalence of prenatal depression and its associated risk factors among pregnant women in Bangalore, Southern India. METHODS: The study was nested within an on-going cohort study. The study participants comprised of pregnant women attending the antenatal clinic at Jaya Nagar General Hospital (Sanjay Gandhi Hospital) in Bangalore. The data was collected using standardised questionnaires. Edinburgh Postnatal Depression Scale (EPDS), Multidimensional Scale of Perceived Social Support Scale (MSPSS), Revised Dyadic Adjustment Scale, The Modified Conflict Tactics scale, Modified Kuppuswamy socio economic scale, Pregnancy related anxiety Scales were used. RESULTS: Of the 280 pregnant mothers, the proportion of them who screened positive for prenatal depression was 35.7%. Presence of domestic violence was found to impose a five times higher and highly significant risk of developing prenatal depression among the respondents. Pregnancy related anxiety was also found to be a positive predictor of prenatal depression. Presence of catastrophic events in the past one year was found to impose a two times higher and significant risk of developing prenatal depression among the respondents. CONCLUSION: The present study showed a higher prevalence of prenatal depression among the study participants which is suggestive of the public health importance in the study region. Health care plans therefore can include screening and diagnosis of prenatal depression in the antenatal care along with other health care facilities provided.